The Oxidation Cascade of a Rare Multifunctional P450 Enzyme Involved in Asperterpenoid A Biosynthesis - Huang, Hui-Yun; Huang, Jia-Hua; Wang, Yong-Heng; Hu, Dan; Lu, Yong-Jun; She, Zhi-Gang; Chen, Guo-Dong; Yao, Xin-Sheng; Gao, Hao (Frontiers in Chemistry, 2021)
The cytochrome P450 enzymes (P450s or CYPs) are heme-containing enzymes which catalyze a wide range of oxidation reactions in nature. In our previous study, a rare multifunctional P450 AstB was found, which can dually oxidize two methyl groups (C-19 and C-21) of preasperterpenoid A to asperterpenoid A with 3-carboxyl and 11-hydroxymethyl groups. However, the oxidation order of C-19 and C-21 catalyzed by AstB is unclear. In order to reveal this oxidation order, the probable pathways catalyzed by AstB were proposed, and the oxidation order of C-19 and C-21 was conducted to the quantum chemistry calculation. The potential intermediates (three new asperterpenoids D‒F, 1‒3) were obtained through the extract of the transformant strain fermented with optimized condition and artificial reduction from asperterpenoid A. Based on detecting the obtained asperterpenoids existing or not in the extract of the transformant strain by LC-MS, the reaction mechanism catalyzed by AstB was revealed. Furthermore, the mPTPB inhibition of obtained asperterpenoids was evaluated, and the structure-activity relationship of C-19 and C-21 with different degree of oxidation in asperterpenoids as mPTPB inhibitors was also proposed.